Evidence of chikungunya virus infection among febrile patients seeking healthcare in selected districts of Tanzania. Issue 1 (1st January 2018) - Kinimi, Edson; Shayo, Mariana J.; Patrick, Bisimwa N.; Angwenyi, Samuel O.; Kasanga, Christopher J.; Weyer, Jacqueline; Jansen van Vuren, Petrus; Paweska, Janusz T.; Mboera, Leonard E.G.; Misinzo, Gerald
ABSTRACT: Introduction : Chikungunya virus (CHIKV) infection is an emerging mosquito-borne disease that has been associated with frequent epidemics in the world. However, there is a dearth of information on its magnitude and associated risk factors in Tanzania. Objective : A study was conducted to determine seroprevalence of CHIKV among febrile patients seeking medical care at health facilities in Karagwe, Sengerema, Kilombero and Kyela districts. Methods : Structured questionnaires were administered and 728 serum samples were collected between May and June, 2015 and tested for the presence of CHIKV-IgM and IgG-specific antibodies using Enzyme-linked immunosorbent assay. Results and discussion : The common clinical characteristics exhibited by outpatients were fever, headache and joint pains (100%, 70%, and 68.3% respectively). Out of 728 outpatients screened for CHIKV, 105 (14%) tested CHIKV IgG positive whilst 11 (1.5%) tested CHIKV IgM positive. Chikungunya seropositivity was significantly higher than previously reported in Tanzania. The most affected age group was 20–29 years. Our results indicate that CHIKV infection is prevalent and contributes to the burden of febrile illnesses in Tanzania. The seroprevalence varies between districts, reflecting variation in mosquito vector transmission dynamics in different parts of the country. Abbreviations: CHIKV: Chikungunya virus; EDTA: Ethylenediaminetetraacetic acid; ELISA: Enzyme-linked immunosorbent assay; IgG: Immunoglobulin G; IgM: Immunoglobulin M; NIMR: National Institute for Medical Research; RU: Relative Units; SACIDS: Southern African Centre for Infectious Disease Surveillance; USA: United States of America